Modified synthesis of edge scrolled reduced graphene oxide with high surface area - R. Rajesh, K. Balkis Ameen, K. Rajasekar (Universiti Pendidikan Sultan Idris, 2016)
Modified synthesis of edge scrolled reduced graphene oxide with high surface area by R. Rajesh, K. Balkis Ameen, K. Rajasekar,